Diagnóstico de potenciliade das unidades ambientais na bacia do Rio Capivara, Botucatu - SP - Carrega, Ellen Fittipaldi Brasílio; Campos, Sergio [UNESP]; Nardini, Rafael Calore; Garcia, Yara Manfrin; Felipe, Andrea Cardador (My University, 2015)
This work has the objective to elaborate the potentialities of the farming expand diagnosis of the Capivara River Hydrographic basin, in the Botucatu – SP municipal district, to obtain an interpretation of the system actual situation through the historical trajectory and possible evolution with the assistance of the SIG Ilwis 3.4 and orbital images CBERS 2B, in the pancromatics bands, obtained in 12/07/2008. The potentialities of the farming expand diagnosis was obtained through the physical mean modeling, of the farming expand presents in the studied environment and shows possible line actions to minimize the impacts e reach a sustainable development to the region. The Capivara river basin presents more than 70% of your areas occupied by the anthropic expanding, with the extensive farming predominance, forestall planting, orange and sugar cane. In the potentiality diagnostic analyses notes the good quality of the basin to the farming expand, except the region comprehended by the Botucatu Cuesta and the meadows area. The basin until has a good environmental quality and this diagnosis must serve for a start point to the realization of the territorial ordination as quick as possible to the environment conditions finds remains the same, granting the recovery capability.

Este trabalho tem como objetivo elaborar o diagnóstico de potencialidade da bacia hidrográfica do Rio Capivara, Município de Botucatu - SP, para obter uma interpretação da situação atual do sistema a vista de sua trajetória histórica e evolução previsível com o auxilio do SIG Ilwis 3.4 e imagens orbitais CBERS 2B, nas bandas pancromáticas, obtidas no dia 12/07/2008. O diagnóstico de potencialidade foi obtido através da modelagem do meio físico e desdobramento agropecuário presentes no ambiente de estudo e aponta possíveis linhas de ação para minimizar os impactos e alcançar o desenvolvimento sustentável da região. A bacia do rio Capivara apresenta mais de 70% da sua área ocupada por desdobramentos antrópicos, com um predomínio da pecuária extensiva, plantação florestal, laranja e cana-de-açúcar. Na análise do diagnóstico de potencialidade percebe-se que a bacia tem uma boa qualidade para o desdobramento de atividades agropecuárias, excetuando a região compreendida pela Cuesta de Botucatu e as áreas de várzea. A bacia ainda possui uma boa qualidade ambiental e esse diagnóstico deve servir de ponto de partida para a realização do ordenamento territorial o mais urgente possível para que as condições encontradas ainda sejam as mesmas, garantindo sua capacidade de recuperação.
Potentiality diagnosis of the environmental units of Capivara River basin, Botucatu - SP
Keywords: Planning; Environmental; Use and occupation of the soil; Agriculture diagnosis potentiality; Ordenamento territorial; Uso e ocupação do solo; Diagnóstico de potencialidade agropecuária